The Mosquito Coast - Theroux P. Paul (Penguin Readers Level 4)
Allie Fox hates the United States and he hates the twentieth century. He takes his wife and children to the jungle in Honduras to find a new, simpler way of living. But things go wrong, and their lives become much worse and more frightening than anything back home.